2020
DOI: 10.1111/rec.13314
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of retired agricultural land to wetland mitigates greenhouse gas emissions

Abstract: Retired farmland restoration is increasingly seen as a valuable opportunity to improve ecosystem functions in sensitive regions. For example, with expected mass retirement of cranberry farms in New England, there is increasing interest in restoring retired cranberry farms back to wetlands. To understand how restoration of retired cranberry farms to wetland ecosystems influences climate-related ecosystem functions, we assessed methane and carbon dioxide emissions from different post-farming management options, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 37 publications
1
2
1
Order By: Relevance
“…The trend of oxidized redox and low biological activity in the lab tests is in direct contrast with field observations, where high oxidation correlates with high respiration (Bartolucci et al, 2021). However, in field conditions, the redox was changing over time (with soil drying) and in our observations the redox changed between samples in an artificial drying-rewetting experiment.…”
Section: Redox Complements But Does Not Replace Other Measures Of Soi...contrasting
confidence: 96%
See 1 more Smart Citation
“…The trend of oxidized redox and low biological activity in the lab tests is in direct contrast with field observations, where high oxidation correlates with high respiration (Bartolucci et al, 2021). However, in field conditions, the redox was changing over time (with soil drying) and in our observations the redox changed between samples in an artificial drying-rewetting experiment.…”
Section: Redox Complements But Does Not Replace Other Measures Of Soi...contrasting
confidence: 96%
“…In fully aerobic soils, oxygen serves as the electron acceptor, resulting in the production of CO 2 and H 2 O. The redox potential is controlled by the rates of reduction and oxidation processes in soil and is connected to soil respiration, for example in rewetted agricultural soils, where redox is a strongly correlated predictor of CO 2 flux (Bartolucci et al, 2021). Based on this, redox could be a promising indicator for soil carbon cycle (labile carbon pools) and structure (oxygen availability), two key components of soil health (Kibblewhite et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Increases in C and N stocks were smaller than increases in soil percent C and N because there was a concurrent decrease in soil bulk density and hence surface soil mass in C and N-rich surface soil layers. Soil percent C was similar to that observed in other active and actively restored former cranberry bogs (Bartolucci et al 2021). The changes to soil percent C and N in 21-49 year-old retired bog beds were generally similar to the changes observed in 30-35 year-old and 50-55 year-old restored wetlands in central New York (Ballantine et al 2009).…”
Section: Soil and Vegetation C Stockssupporting
confidence: 76%
“…In previous studies, we have described the desirable impacts that active ecological restoration of retired cranberry farms has on both biogeochemical characteristics [ 50 , 51 ] and microbial community structure [ 11 ]. Here, we found that flooding also promotes beneficial wetland functions, even exceeding wetland restoration for soil organic matter formation and cation exchange capacity.…”
Section: Discussionmentioning
confidence: 99%